"The Great Gabbo" - Cruze, James, 1884-1942; Von Stroheim, Erich, 1885-1957; Compson, Betty, 1897-1974; Hecht, Ben, 1894-1964.; James Cruze Productions; Cinetel Films ([Los Angeles, CA] : James Cruze Inc., 1929)
A temperamental ventriloquist who can only express himself through his dummy. He becomes tortured by the conflicting nature of his personality, which eventually drives him insane.
Adapted from the story "The great Gabbo" by Ben Hecht.
Eric Von Stroheim, Betty Compson, Donald Douglas, Margie (Babe) Kane.
Photography, Ira Morgan; music director, Howard Jackson.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Ventriloquists -- Drama; Feature films; Internet videos; Streaming video